Tribological behaviour of quenched and tempered, and austempered ductile iron at the same hardness level - Haseeb, A.S. Md. Abdul; Islam, Md. Aminul; Bepari, Md. Mohar Ali (Elsevier, 2000)
The tribological behaviour of ductile iron heat-treated by two different procedures viz. quenching and tempering, and austempering to an identical matrix hardness of 445 KHN is compared. Wear tests were carried out using a pin-on-disc type apparatus under dry sliding conditions at a linear speed of 1.18 m s(-1). Applied load and sliding distance in the range of 7.5-30 N and 2 x 10(4)-6 x 10(4) m, respectively, were used. It was observed that under all test conditions, austempered ductile iron exhibits a better wear resistance than quenched and tempered ductile iron, although both have an identical chemical composition and matrix hardness. The relative superiority of austempered ductile iron becomes even more pronounced at higher load and longer sliding distance. Microhardness measurement below the wear scar reveals that the hardness of austempered ductile iron increases while that of quenched and tempered iron decreases during the wear process. Metallographic study of the worn surfaces and X-ray investigation on wear debris indicate that oxidational wear is operative in both the samples. Stress-induced martensitic transformation of retained austenite as well as strain hardening of bainitic ferrite are thought to contribute to the improved wear performance of austempered ductile iron. (C) 2000 Elsevier Science S.A. All rights reserved.